2019
DOI: 10.1097/olq.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on Expedited Partner Therapy: A Content Analysis of Informational Materials for Providers, Pharmacists, Patients, and Partners

Abstract: This report was prepared at the direction of John M. Douglas, Jr., M.D., Director, Division of STD Prevention, NCHSTP, CDC. It summarizes the available literature on expedited partner therapy (EPT) for the management of the partners of persons with STD and interprets the results. It also incorporates perspectives gained from two expert consultations, one that predominantly addressed the scientific evidence related to EPT and a second that emphasized operational issues that will affect implementation of EPT. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Our overall patient acceptance rate of EPT was similar or higher than that in other studies 3,18–20 . The addition of literacy level-appropriate bilingual patient education, provider education, and pharmacy policy updates addressed issues previously identified as potential barriers to EPT uptake 7,21 . The increase in EPT refusals from patients in the postintervention group was 8% (25/308) and could be because of an increased offering of EPT prompted by clinical decision support and institutional policy changes versus referring patients to an outside provider.…”
Section: Discussionsupporting
confidence: 58%
“…Our overall patient acceptance rate of EPT was similar or higher than that in other studies 3,18–20 . The addition of literacy level-appropriate bilingual patient education, provider education, and pharmacy policy updates addressed issues previously identified as potential barriers to EPT uptake 7,21 . The increase in EPT refusals from patients in the postintervention group was 8% (25/308) and could be because of an increased offering of EPT prompted by clinical decision support and institutional policy changes versus referring patients to an outside provider.…”
Section: Discussionsupporting
confidence: 58%
“…One recent study examining health department Web sites found that EPT informational materials had little information for index patients, and what was available was inadequate in terms of readability and content. 29 Future research should therefore also examine how implementing new intervention strategies could increase patients' PDPT acceptance. It must also be noted that problems with EPT/PDPT uptake among health care providers are well documented and include lack of knowledge, perceptions of suboptimal care, and legal challenges.…”
Section: Discussionmentioning
confidence: 99%
“…As a next step, health care providers' standard of practice regarding their provision of PDPT, including patient communication and health education materials, should be assessed. One recent study examining health department Web sites found that EPT informational materials had little information for index patients, and what was available was inadequate in terms of readability and content 29 . Future research should therefore also examine how implementing new intervention strategies could increase patients' PDPT acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…The discussion guide, informed by prior research, 7,13 addressed the following: provider demographics, description of clinical setting and patients, practices in genital CT diagnosis/ treatment, partner management, perception of EPT, and changes needed for EPT implementation, for example, educational meetings, protocols, and internal champions (Appendix 1, http:// links.lww.com/OLQ/A583). 14 The discussion guide was piloted with 5 providers before launch; these data informed revisions but were not included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Expedited partner therapy is widely permitted across the United States, and two-thirds of state health departments have issued EPT practice guidance for providers. 7,8 Respective to other states, Georgia was a late adopter of legislation permitting EPT (May 2017), 8 and provider guidance on how to practice EPT in GA was issued only recently (November 2019). Although issuing EPT guidance is an important step, passive dissemination of guidance does not change clinical practice.…”
mentioning
confidence: 99%